2018
DOI: 10.3390/jof4020062
|View full text |Cite
|
Sign up to set email alerts
|

Sporotrichosis: From KOH to Molecular Biology

Abstract: Sporotrichosis is a cosmopolitan, chronic granulomatous mycosis, acquired by traumatic inoculation and caused by Sporothrix schenckii complex. Several methods of diagnostic are available, from KOH to molecular biology. In this review, we describe from the simplest (clinical diagnosis) to the most advanced diagnostic techniques (molecular biology).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 39 publications
0
63
0
Order By: Relevance
“… 10 The gold standard for diagnosis of Sporothrix was culture positive after incubation on Sabouraud dextrose agar for 5–8 days. 11 However, the infection lodge deep in host tissue, reside in cyst form, and the culture was frequently negative. Then tissue biopsy was usually required.…”
Section: Discussionmentioning
confidence: 99%
“… 10 The gold standard for diagnosis of Sporothrix was culture positive after incubation on Sabouraud dextrose agar for 5–8 days. 11 However, the infection lodge deep in host tissue, reside in cyst form, and the culture was frequently negative. Then tissue biopsy was usually required.…”
Section: Discussionmentioning
confidence: 99%
“…The laboratory diagnosis of the disease in felines begins with the cytology by imprint of the lesions, followed by isolation of the agent in culture. The latter is considered the gold standard [9]. Other methods, such as those based on investigation of serum antigens and antibodies, have been studied since the 1970s [10,11], although none involved a laboratory routine or proved to be clinically validated.…”
Section: Introductionmentioning
confidence: 99%
“…There are cases in which this disease is not suspected and culture tests are therefore not performed at the time of skin biopsy. In addition, microscopic examination after applying potassium hydroxide to the purulent exudate from the lesion or histopathological studies is not informative enough to establish a diagnosis of sporotrichosis, as the classical cigar‐shaped fungal cells or asteroid bodies characteristic of sporotrichosis are detected in only a small number of positive samples …”
Section: Introductionmentioning
confidence: 99%
“…In addition, microscopic examination after applying potassium hydroxide to the purulent exudate from the lesion or histopathological studies is not informative enough to establish a diagnosis of sporotrichosis, as the classical cigar-shaped fungal cells or asteroid bodies characteristic of sporotrichosis are detected in only a small number of positive samples. 5 In 2003, Hu et al 6 reported PCR diagnosis of Sporothrix infection from skin tissue. According to their method, a skin tissue sample taken at biopsy was frozen, then DNA was extracted from the cryopreserved tissue, and nested PCR was performed using primers specific for Sporothrix.…”
Section: Introductionmentioning
confidence: 99%